Development of Computational Thinking Test Instrument for Evaluation of STEM Learning in Elementary School - Ismail, Mochamad Tubagus; Setyawan, Dedy; Alifulloh, Wenda (International Conference on Elementary Education, 2024)
STEM-based learning is one of the efforts in developing 21st century skills today. The characteristic of STEM approach is the strengthening of computational thinking skills that should be able to prepare individuals in facing society 5.0. This research aims to provide an overview of the computational thinking test instrument as an assessment solution in STEM learning. Through the development research method, this thinking test instrument was tested on grade VI elementary school students in the Kertasari District of Bandung Regency. The results showed that the computational thinking skills test instrument based on five indicators has a good level of validity and reliability to be implemented as an element of cognitive assessment assessment in STEM learning in elementary schools on the material components of living things and the surrounding environment.